2024
DOI: 10.1002/adma.202307585
|View full text |Cite
|
Sign up to set email alerts
|

Chlorella‐Loaded Antibacterial Microneedles for Microacupuncture Oxygen Therapy of Diabetic Bacterial Infected Wounds

Shuna Gao,
Yu Rao,
Xiaowei Wang
et al.

Abstract: Hypoxia and infection are urgent clinical problems in chronic diabetic wounds. Herein, living Chlorella‐loaded poly(ionic liquid)‐based microneedles (PILMN‐Chl) were constructed for microacupuncture oxygen and antibacterial therapy against methicillin‐resistant Staphylococcus aureus (MRSA)‐infected chronic diabetic wounds. The PILMN‐Chl can stably and continuously produce oxygen for more than 30 h due to the photosynthesis of the loaded self‐supported Chlorella. By combining the barrier penetration capabilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…In addition, granulation tissue plays a critical role in the regenerative repair process of wounds accompanied by inflammation. 15 The immature tissue in the PBS groups was the largest, in line with results in Figure 3b. The epidermis and dermis of wound areas in the MN group were thinner than those of the PBS group.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…In addition, granulation tissue plays a critical role in the regenerative repair process of wounds accompanied by inflammation. 15 The immature tissue in the PBS groups was the largest, in line with results in Figure 3b. The epidermis and dermis of wound areas in the MN group were thinner than those of the PBS group.…”
Section: Resultssupporting
confidence: 86%
“…H&E staining further revealed that the area of unhealed wounds in the PBS group was much larger than that of treated groups. In addition, granulation tissue plays a critical role in the regenerative repair process of wounds accompanied by inflammation . The immature tissue in the PBS groups was the largest, in line with results in Figure b.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…25 The hyperglycemic microenvironment of diabetic wounds increases the susceptibility of the wound to microbial infection and further results in impaired angiogenesis and dysfunction of macrophages, delaying wound healing. 26 Eliminating local wound infection not only is beneficial for wound healing but can also relieve pain and reduce the risk of further complications such as sepsis. 27 Wound dressings serve as a primary and effective means of shielding injuries from microbial infection.…”
Section: ■ Introductionmentioning
confidence: 99%